2010
DOI: 10.1016/j.physa.2009.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of agent-based models in markets with continuous double auction mechanism

Abstract: Real world markets display power-law features in variables such as price fluctuations in stocks. To further understand market behavior, we have conducted a series of market experiments on our web-based prediction market platform which allows us to reconstruct transaction networks among traders. From these networks, we are able to record the degree of a trader, the size of a community of traders, the transaction time interval among traders and other variables that are of interest. The distributions of all these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…Jiang and Zhou reveal that the daily trading networks in Shenzhen stock market exhibit patterns of power-law degree distributions and disassortative architectures [2]. Tseng et al uncover a power-law correlation between the average degree and the size of placed orders [3,4]. Wang et al find that the trading networks in the Shanghai Futures Market exhibit similar features such as scale-free, small-world effect, hierarchical organization, and power-law betweenness distribution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Zhou reveal that the daily trading networks in Shenzhen stock market exhibit patterns of power-law degree distributions and disassortative architectures [2]. Tseng et al uncover a power-law correlation between the average degree and the size of placed orders [3,4]. Wang et al find that the trading networks in the Shanghai Futures Market exhibit similar features such as scale-free, small-world effect, hierarchical organization, and power-law betweenness distribution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tseng et al () conducted a series of experiments on a web‐based market platform to study the properties of real financial markets. In their work, three strategies were built: the ZI, ZIP and the Gjerstad–Dickhaut (GD) auction strategy.…”
Section: Related Workmentioning
confidence: 99%
“…This relies on the GD agents forming a belief and payoff function. Tseng et al () found that although the ZI strategy is the most naive, ZI agents are the best among the ZIP and GD strategies in terms of describing the stylized facts observed in real financial markets. Their study emphasized the importance of a continuously evolving dynamic trading strategy that implies features similar to that of the ZI model.…”
Section: Related Workmentioning
confidence: 99%
“…An alternative is to use an agent-based approach. This has become a widely used tool in the area of complex systems [66,60,69,18,17,32,58]. For example, agent-based models have been used for modeling many types of cooperative behavior [31,56,14,11,24].…”
Section: Agent-based Modelsmentioning
confidence: 99%